2017
DOI: 10.1016/j.eurpsy.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits in adults age 60 and above with attention deficit hyperactivity disorder

Abstract: The results are in line with models of heterogeneity that have identified different neuropsychological subtypes in ADHD as well as a subgroup of patients without any clear neuropsychological deficits. For older adults with ADHD, it will be important to assess their functioning across time as normal aging is related to memory decline and these patients could therefore end up with severe deficits as they grow older, which in turn could have serious negative effects on daily life functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 121 publications
(217 reference statements)
5
35
2
1
Order By: Relevance
“…With regard to older adulthood, much fewer studies exist and findings are more mixed. A previous study using the same sample as the present study showed that older adults with ADHD differed from healthy controls with regard to working memory, inhibitory control, switching, but not planning [15]. However, another population-based study found that older adults with ADHD only differed from controls with regard to working memory [16].…”
Section: Adhd In Older Adulthoodcontrasting
confidence: 46%
See 1 more Smart Citation
“…With regard to older adulthood, much fewer studies exist and findings are more mixed. A previous study using the same sample as the present study showed that older adults with ADHD differed from healthy controls with regard to working memory, inhibitory control, switching, but not planning [15]. However, another population-based study found that older adults with ADHD only differed from controls with regard to working memory [16].…”
Section: Adhd In Older Adulthoodcontrasting
confidence: 46%
“…However, another population-based study found that older adults with ADHD only differed from controls with regard to working memory [16]. It should also be noted that studies using person-oriented analyses have shown that only a subgroup of individuals diagnosed with ADHD has clear executive deficits, and this has been demonstrated in both childhood [17,18] and adulthood [15]. This heterogeneity in neuropsychological functioning may explain why some individuals with ADHD have more impaired daily life functioning than others.…”
Section: Adhd In Older Adulthoodmentioning
confidence: 99%
“…This finding is in line with the dual pathway hypothesis (Sonuga-Barke, 2003). In addition, it has been shown that the overlap between working memory, inhibition, and speed of processing is larger in younger (18-45 years) than in older adults (60-75 years), with 11% of older adults and 30% of younger adults showing deficits in all three domains (Thorell, Holst, et al, 2017). There are very few studies examining the extent to which emotion dysregulation overlaps with other neuropsychological deficits in relation to adult ADHD.…”
Section: Overlap Between Different Neuropsychological Deficits In Adhdsupporting
confidence: 87%
“…2,3 A cross-national prevalence of 2.8% has been reported for ADHD in young to middle adulthood. [8][9][10] Regarding cognitive functioning, results are less clear with one recent study showing lower performance on several neuropsychological measures among older adults with ADHD compared with healthy matched controls, 11 while another study demonstrated no differences after controlling for comorbid depression. 6,7 Adults with ADHD aged 60 years and older have been found to have similar impairments as younger adults with ADHD in terms of comorbid psychiatric disorders (eg, mood and anxiety disorders), equally lower educational achievements, impaired social functioning, and lower quality of life.…”
mentioning
confidence: 99%
“…6,7 Adults with ADHD aged 60 years and older have been found to have similar impairments as younger adults with ADHD in terms of comorbid psychiatric disorders (eg, mood and anxiety disorders), equally lower educational achievements, impaired social functioning, and lower quality of life. [8][9][10] Regarding cognitive functioning, results are less clear with one recent study showing lower performance on several neuropsychological measures among older adults with ADHD compared with healthy matched controls, 11 while another study demonstrated no differences after controlling for comorbid depression. 12 Thus, ADHD has been shown to be a serious condition with large functional impairments also in older adults, and this calls for validation of psychometric assessment tools for ADHD in this age group.…”
mentioning
confidence: 99%